One parallel in early oxidation stages of Cr-containing alloys - Robert Wonneberger; Jonathan Apell; Martin Seyring; Wolfgang Wisniewski; Hartmut Stöcker; Andreas Undisz (Materials Today Advances)
The first oxide crystals formed during the early oxidation stages are considered to be the critical stage for the corrosion resistance of metallic materials against oxidants. The corrosion resistance of Cr-containing alloys is generally linked to Cr-rich oxide layers; however, their applicative performance varies remarkably. Classical models addressing the formation of these layers fail to account for the associated dynamics. We present evidence that Cr-containing Fe-, Co-, Ni-base and high-entropy alloys exhibit a parallel phenomenon during the initial transient stage: two-layered, multicompositional oxide grains with Cr always occupying the inner layer adjacent to the bulk. We propose that oxide growth occurs at a single location which allows to consistently incorporate all presented results. Oxide layer growth occurs inside the oxide grains at the transition to the Cr enrichment, independent of the initial oxide crystal structure. A potential multi-scale model for oxidation requires implementing the presented results which emphasizes the dominance of kinetic contributions during the early stages of oxidation.